The Tat Pathway of the Plant Pathogen Pseudomonas syringae is Required for Optimal Virulence - Isabelle Caldelari; Stefan Mann; Casey Crooks; Tracy Palmer (Molecular Plant-Microbe Interactions, 2006)
Pseudomonas syringae is a gram-negative bacterium that infects a number of agriculturally important plant species. The ability of the organism to deliver virulence factors across the plant cell wall is a key to its pathogenicity. Deletion mutants in the twin arginine translocation (Tat) pathway of two pathovars of P. syringae, pvs. tomato DC3000 and maculicola ES4326, displayed a range of pleiotropic phenotypic changes, such as defects in fluorescent siderophore production, a decrease in sodium dodecyl sulfate and copper resistance, and a significant loss in fitness using Arabidopsis thaliana or tomato as plant hosts. The genome sequence of P. syringae pv. tomato DC3000 encodes a number of potential virulence factors that are predicted to be translocated via the Tat pathway, including several proteins involved in iron scavenging (two siderophore receptors, PSPTO3474 and PSPTO3294, and an aminotransferase, PSPTO2155, involved in siderophore biosynthesis). Further candidates for Tat-dependent pathogenicity determinants include the homologs of a cell wall amidase (PSPTO5528), an enzyme involved in periplasmic glucans biosynthesis (PSPTO5542), and two putative phospholipases (PSPTO3648 and PSPTOB0005). Translocation of the putative amidase, aminotransferase, glucans biosynthetic enzyme, and the two phospholipases, but not the two siderophore receptors, is shown to be dependent on the Tat pathway. Strains deleted for the genes encoding the probable aminotransferase and amidase enzymes are significantly less infectious than the wild type. We conclude that the incremental effects due to the failure to correctly localize at least two, and possibly more, Tat substrates gives rise to the attenuated fitness phenotype of the P. syringae pv. tomato DC3000 tat strain.